1994
DOI: 10.1007/bf01006814
|View full text |Cite
|
Sign up to set email alerts
|

[3H]Histamine uptake and release by astrocytes from rat brain: Effects of sodium deprivation, high potassium, and potassium channel blockers

Abstract: Histamine transport has been characterized in cultured astroglial cells of rat brain. The kinetics of [3H]-histamine uptake yielded a Km of 0.19 +/- 0.03 microM and a Vmax of 3.12 +/- 0.75 pmol X mg protein-1 X min-1. Transport system revealed high affinity for histamine and an approximately ten times higher capacity than that shown in cultured glial cells of chick embryonic brain. Ouabain which interferes with utilization of ATP to generate ion gradients, and the replacement of Na+ with choline inhibited the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…Yet, we could demonstrate that they do not inhibit histamine uptake via Ha receptor blockade [13]. It was therefore plausible that hematopoietic progenitor cells possessed a means of histamine transport, as described for a few other cell types such as astrocytes, endothelial and glial cells [16][17][18].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, we could demonstrate that they do not inhibit histamine uptake via Ha receptor blockade [13]. It was therefore plausible that hematopoietic progenitor cells possessed a means of histamine transport, as described for a few other cell types such as astrocytes, endothelial and glial cells [16][17][18].…”
Section: Resultsmentioning
confidence: 99%
“…Although we have provided evidence that this phenomenon is not mediated by classical histamine receptors, Ha receptor antagonists, such as thioperamide and MR16155, are potent inhibitors. Conversely to the polyamine transport system, which exists in numerous cell types and has been extensively studied [14,15], histamine transport seems to be restricted to astrocytes, endothelial and glial cells, and is still poorly understood [16][17][18]. It has been suggested that astrocytes could use the same means of transport for histamine uptake and release [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A histamine uptake mechanism has been identified in chicken and rat cerebral astrocytes and also in cerebral endothelial cells on the basis of experiments in which virtually homogeneous cell cultures were incubated with the radiolabeled amine (Huszti et al 1990(Huszti et al , 1994Huszti and Balogh, 1995). The initial rate of histamine uptake reflecting a high affinity interaction that could be described by Michaelis-Menten kinetics, required external Na 1 and was inhibited by histamine analogues (2-methylhistamine, 4-methylhistamine, impromidine), desmethylimipramine and depolarizing agents (barium chloride and sparteine) but also by heavy metals (Pb 11 and Hg 11 ) in low 1-10 µM concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…This take up is temperature-dependent and requires sodium exchange for optimal function. It was observed in astrocytes, endothelial and glial cells [7][8][9].…”
Section: Introductionmentioning
confidence: 99%